Kajian Komunikasi Pengurus Pentas Dalam Produksi Puteri Gunung Ledang 2019 - Nur Shafiqah Jasmin, Ja’afar (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study was conducted to expose the use of communication theory (behaviorism) in a production. The methodology used in completing this study is using a qualitative method. Researchers obtain information and data through the results of reading and observation throughout the production. Observations were carried out befire, during, and after production.